Comparison of biodiesel using potassium hydroxide and magnesium oxide as catalyst - Wan Noralwani Wan Zamry, 1987-; Abdul Rahim Yacob; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2009